Efeitos da exposição crônica a estrona na gametogênese e reprodução do zebrafish (Danio rerio) - Yves Moreira Ribeiro (2022)
Estrone is an important environmental contaminant in waters of countries that have livestock as a relevant economic activity because its leaching from the excreta of poultry, pigs, cattle and horses. The objective of the present study was to analyze the effects of the estrone exposure at environmentally relevant concentrations on gametogenesis and reproduction of zebrafish (Danio rerio). After exposure to estrone at concentrations of 20, 200 and 2000 ng/L for 49 days, gametogenesis and reproduction of zebrafish were analyzed through morphometric and molecular analyses. In the gonads, the proportion (%) of tissue components, dosage of 11-ketotestosterone and estradiol, cell proliferation and death, expression of IGF1, IGF2, IGF1R and iNOS were analyzed and the production of nitric oxide was evaluated. In addition, semen quality parameters in males, egg production by females and fertilization rate were evaluated. The results showed that estrone exposure was responsible to changes in the sex steroids production, IGF signaling pathway and increased nitric oxide production that led to changes in the proportion of germ cells and gonadal somatic components. As a consequence, egg production was reduced in all estrone-exposed groups together with reduced progressive motility, curvilinear velocity, and beat cross frequency in the sperm of 20 and 2000 ng/L E1 groups, and significantly lower fertilization rate in the 200 and 2000 ng/L groups. The results of the present study indicate that estrone exerts deleterious effects on the testes, ovaries and reproduction of fish, even at environmentally relevant concentrations, and that its concentrations in water should be monitored for the conservation of this group of vertebrates.